Information, Trading, and Product Market Interactions: Cross‐sectional Implications of Informed Trading - TOOKES, HEATHER E. (Journal of Finance, 2008)
ABSTRACT I present a simple model of informed trading in which asset values are derived from imperfectly competitive product markets and private information events occur at individual firms. The model predicts that informed traders may have incentives to make information‐based trades in the stocks of competitors, especially when events occur at firms with large market shares. In the context of 759 earnings announcements, I use intraday transactions data to test the hypothesis that net order flow and returns in the stocks of nonannouncing competitors have information content for announcing firms.